From schemes to the teacher`s pedagogical creativity in cyberculture = Od schematu do twórczości pedagogicznej nauczyciela w cyberkulturze - Magda-Adamowicz, Marzenna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article discusses changes in external conditions of the functioning of contemporary man, including the teacher. The author pays attention to the changes connected with the development of media and electronic devices used for the processing of information and for communication. What is more, new information and verified knowledge is constantly added. School, still a traditional place of their transfer, cannot ignore these new knowledge sources. They are accessible and used by pupils, to whom operation of devices does not pose difficulties. With the same, contemporary teachers are expected to raise their qualifications in the field of cyberculture through professional improvement and selfeducation.
Keywords: teacher; pedagogical creativity; nauczyciele; twórczość pedagogiczna